2014
DOI: 10.14411/fp.2014.011
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan gill parasites of the Atlantic bluefin tuna Thunnus thynnus (Linnaeus) (Osteichthyes: Scombridae) from the Mediterranean and their possible use as biological tags

Abstract: the gills of 63 specimens of the Atlantic bluefin tuna Thunnus thynnus (linnaeus) (osteichthyes: scombridae) from three localities of the Mediterranean (sardinian, tyrrhenian and levantine seas) were examined for metazoan parasites. the parasite fauna of T. thynnus from the sea of sardinia included 11 species: five didymozoid trematodes, three capsalid and one hexostomid monogeneans, and one caligid and one pseudocycnid copepods. Four didymozoids were found in fish from the levantine sea and only one didymozoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…worldwide were used to assess the dissimilarity between the parasite faunas of the head region of the bullet and frigate tunas from four geographical regions: A. thazard from the Atlantic Ocean (data from Vervoort, 1965;Fuentes Zambrano, 1997;Mogrovejo et al, 2004;Chisholm & Whittington, 2007), A. thazard from the Indian Ocean (data from Silas, 1962;Mogrovejo et al, 2004;Chisholm & Whittington, 2007), A. thazard from the Pacific Ocean (data from Silas, 1962;Yamaguti, 1970;Mogrovejo et al 2004;Chisholm & Whittington, 2007) and A. rochei from the Mediterranean Sea (present results). Parasite fauna dissimilarity was evaluated with the Marczewski -Steinhaus distance ('cc' method, 'betadiver' function, 'vegan' library of the R-software) and the Bray -Curtis index (' -1' method, 'betadiver' function, 'vegan' library of the R-software) (Culurgioni et al, 2014;Mele et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…worldwide were used to assess the dissimilarity between the parasite faunas of the head region of the bullet and frigate tunas from four geographical regions: A. thazard from the Atlantic Ocean (data from Vervoort, 1965;Fuentes Zambrano, 1997;Mogrovejo et al, 2004;Chisholm & Whittington, 2007), A. thazard from the Indian Ocean (data from Silas, 1962;Mogrovejo et al, 2004;Chisholm & Whittington, 2007), A. thazard from the Pacific Ocean (data from Silas, 1962;Yamaguti, 1970;Mogrovejo et al 2004;Chisholm & Whittington, 2007) and A. rochei from the Mediterranean Sea (present results). Parasite fauna dissimilarity was evaluated with the Marczewski -Steinhaus distance ('cc' method, 'betadiver' function, 'vegan' library of the R-software) and the Bray -Curtis index (' -1' method, 'betadiver' function, 'vegan' library of the R-software) (Culurgioni et al, 2014;Mele et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…and Grammatorcynus spp.). Concerning the differences in the ectoparasite fauna of S. colias from the eastern and western Mediterranean Seas, they can be due to the different oceanographic conditions of the shallow water of these basins (Robinson et al 2001) as it has also been reported for other fish (Marzoug et al 2012;Culurgioni et al 2014). (Goto, 1984) 86 (69-95) 5.4 (3.9-7.1) 6.3 (4.8-7.9) Trematoda Didymozoidae Nematobothrium cf.…”
mentioning
confidence: 80%
“…In fact, several didymozoids have been recorded outside their endemic areas (Lester et al 1985;Mele et al 2012), because they cannot leave their hosts, being encysted in the host tissues (Pascual et al 2006). The distance could be a barrier to the spread of these didymozoids between the opposite coasts of the Atlantic Ocean, as also showed for several mazocraeids (K. sprostonae, P. minor); whereas the different oceanographic conditions between the eastern and western Mediterranean Seas (Robison et al 2001;Manca et al 2004), which can support a different macro fauna (Garibaldi 1998), can be an important factor that could explain the different trematode faunas of these basins (Gargouri Ben Abdalah et al 2010;Culurgioni et al 2014). On the bases of the published and present data on the parasites of the head of the four species of the genus Scomber worldwide, a datasheet of presence/absence of parasites by geographical region was created (Tables I-III), making it possible to evaluate the dissimilarity between the parasite faunas of the four mackerel species (Fig.…”
mentioning
confidence: 89%
“…The gills were dissected and the location of eggs and adult parasites was recorded according to Culurgioni et al (2014). To detect the presence of eggs, two filaments (= primary lamellae) of opposite hemibranchs, from five areas along the longitudinal axis of each holobranch were separated (see Fig.…”
Section: Methodsmentioning
confidence: 99%